PREVALENCE OF MICROALBUMINURIA WITH RELATION TO GLYCEMIC CONTROL IN TYPE-2 DIABETIC PATIENTS IN KARACHI - Sheikh, Shehnaz A; Baig, Jawed Altaf; Iqbal, Tehseen; Kazmi, Tahseen; Baig, Muhammad; Husain, Syed Shajee (Journal of Ayub Medical College Abbottabad, 2009)
Background: Diabetes is one of the most common endocrine disorders characterized by hyperglycaemia. Diabetic nephropathy is a consequence of long standing diabetes. The prevalence of microalbuminuria predicts progression to diabetic nephropathy. The present study was conducted to determine the prevalence of microalbuminuria in relation to duration of diabetes, BMI, Serum Creatinine and HbA1c in an ethnic group of Type 2 diabetes mellitus residing in Karachi. Methods: This cross-sectional descriptive study was carried out in a community diabetic centre, located at Garden East Karachi from July to December 2007. One hundred known Type 2 diabetic patients with age 30- 70 years were included in the study. Informed consent and a structured questionnaire of each patient were recorded. Fasting venous blood and morning urine sample was collected for analysis of creatinine, HbA1c and microalbuminuria respectively. Statistical analysis was done using SPSS version 13.0. Pearson correlation was applied to observe association of microalbuminuria with different parameters. All p-values <0.05 were considered as statistically significant. Results: Microalbuminuria had a highly significant correlation with duration of diabetes, serum creatinine (p<0.001), HbA1c (p<0.05) and BMI (p<0.024). A strong correlation exists between age and serum creatinine (r=0.73). Conclusion: The present study found an early onset of microalbuminuria in the selected community which could be due to poor glycaemic control (high HbA1c >7%) or heredity factors. Screening for microalbuminuria and HbA1c test should be done in both newly and already diagnosed Type 2 diabetic patients as an early marker of renal dysfunction and glycaemic control. Keywords: Microalbuminuria, HbA1c, duration, diabetes, Serum Creatinine